(untitled) (Research, Society and Development, 2021)
Orthodontics is a specialty that assesses the growth and development of the face and teeth, preventing and correcting dental malocclusions up to deviations from normal face. Orthodontic treatment causes changes in aesthetics and function, thus impacting patients’ quality of life. The existing protocols for tooth movement consist of the traditional fixed methods using brackets (metallic, plastic or ceramic) and metallic wires, and the invisible removable braces, made of thermoplastic material that present several benefits, such as their aesthetics and facilitating oral hygiene. Thus, this work has the general objective of conducting a literature review of the studies and research carried out in relation to invisible orthodontic appliances and to evaluate the available evidence on the clinical effectiveness of the system. 76 studies were analyzed. It was observed by the review analysis of the articles presented in the study that the system of invisible and removable appliances applied to orthodontic treatment has numerous advantages, therefore, this system has become increasingly demanded and chosen as an option for orthodontic treatment. It is concluded that advances in the quality of aligner materials, accessories and complementary systems, in the use of digital systems for processing initial data, as well as in virtual three-dimensional planning have expanded the range of possibilities of orthodontic treatment with invisible and removable appliances applied to various orthodontic problems, whether of lesser or greater complexity. The system has been widely used and its effectiveness, precision and predictability in treatment are observed in the studies.